(untitled) - Miller, Roger LeRoy (Mason, Ohio, 2007)
The Fifth Edition of Miller and Cross's THE LEGAL ENVIRONMENT TODAY offers your course the AACSB-recommended quality that you demand and a real-world, hands-on learning experience that engages your students in every chapter. Exceeding all expectations-yours and your students', the new edition includes strong guidance in critical thinking and legal reasoning; exceptionally current coverage of ethics, cyberlaw, and corporate responsibility; a superb selection of the latest cases, including 2005 and 2006 decisions; and equally impressive coverage of the landmark cases that continue to steer today's legal environment. Students will find many examples and realistic scenarios where they can use their growing knowledge of the law to resolve legal and ethical issues for themselves.
Keywords: Business law,Law,Luật kinh doanh; United States,United States,Hoa Kỳ